PENGARUH PROFESIONALISME, PENGETAHUAN MENDETEKSI KEKELIRUAN, ETIKA PROFESI, DAN AKUNTABITAS TERHADAP PERTIMBANGAN TINGKAT MATERIALITAS (Studi Pada KAP Aceh, Medan dan Palembang) - Hildayeni Aprilla; Andreas '; Mudrika alamsyah Hasan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The research aims to examine the influence ofprofessionalism, knowledge of error detection, professional ethical, and accountability to the judgment of materiality level. Object of this research were public accountants that registered in Aceh, Medan, and Palembang. There are eighty questionnaires were sent, but only forty two questionnaires are returned. That data are analyzed by multiple regression method and SPSS program version 19. The variables were examined are influence ofprofessionalism, knowledge of error detection, professional ethical and accountability to the judgement of materiality level. The results of this research showed that professionalism has an effect tothe judgement of materiality level with 0,016 significance, knowledge of error detection has an effect to the judgment of materiality level with 0,021 significance, professional ethical has an effect to the judgment of materiality level with 0,003 significance, and accountability has an effect to the judgment of materiality level with 0,019 significance. The results of this research also showed that coefficient determinant is 88,8%.While the remaining influenced by other variables not included in the regression models were not included in this study as organizations culture, external factor and othersKeywords: professionalism, knowledge of error detection, professional ethical, accountability, and the judgment of materiality level